PENINGKATAN KINERJA CONTROL VALVE AKIBAT FENOMENA RESET WINDUP PADA SISTEM REBOILER - Megarini Hersaputri; Yuniarto Yuniarto; Ari Bawono Putranto; Dista Yoel Tadeus; Fakhruddin Mangkusasmito (BERKALA FISIKA, 2022)
One of the important elements of the LPG production process is the control valve. Control valves is almost 90% found in the LPG process. The size of the control valve must have a standard size so that the performance of the control valve is more optimal. Control valve CV1 is a control valve to regulate the flow of steam to reboiler in the distillation column. CV1 at the gas processing plant which is the object of research is experiencing the phenomenon of reset wind up, reset wind up is a phenomenon where the variable control valve process is unable to reach the set point at the indicating point (TIC) even though the control valve has reached 100% opening. The phenomenon of reset wind up on CV1 affects the temperature of the steam used for the reboiler. If the steam produced by the reboiler is not up to separation standard in propane distillation, then the C3 separation is not perfect and will affect the LPG yield. To improve the performance of the control valve, it is necessary to calculate the coefficient valve on the control valve and replace the internal valve parts. From this research, the coefficient value is 591, control valve body type ET-667 with diameter of 8